Creative Trade for Human Development - Kabanda, Patrick (World Bank, Washington, DC, 2016)
In recent years, international trade in creative goods and services has been expanding. But this upward march is not lifting all boats. Although many developing countries are endowed with vast cultural wealth, they still lag behind. In addition, women are not faring well. Much needs to be done to expand creative trade for human development. Suggestions here include implementing a Women Artisan Trade Initiative, creating a cultural trade index, developing appropriate intellectual property initiatives, and considering creative trade in economic diversification strategies.